A longitudinal study of cortical changes and their cognitive correlates in patients followed up after first-episode psychosis. Issue 1 (3rd July 2014) - Gutiérrez-Galve, L.; Chu, E. M.; Leeson, V. C.; Price, G.; Barnes, T. R. E.; Joyce, E. M.; Ron, M. A.
Abstract : Background: Loss of cortical volume in frontotemporal regions occurs in patients with first-episode psychosis (FEP) and longitudinal studies have reported progressive brain volume changes at different stages of the disease, even if cognitive deficits remain stable over time. We investigated cortical changes in patients over the 2 years following their FEP and their associations with clinical and cognitive measures. Method: Twenty-seven patients after their FEP (20 with schizophrenia, seven with schizo-affective disorder) and 25 healthy controls matched for age and gender participated in this study. Magnetic resonance imaging (MRI) was performed on a 1.5-T scanner both at baseline and after 2 years. Area and thickness of the cortex were measured using surface-based morphometry (SBM). Patients also underwent neuropsychological testing at these two time points. Results: Progressive cortical thinning in the superior and inferior frontal and, to a lesser extent, superior temporal cortex was observed in patients. Cortical area remained constant. Cortical thinning was associated with duration of treatment at a trend level and was predicted by baseline measures of IQ and working memory. Cortical thinning occurred in the absence of clinical or cognitive deterioration. Conclusions: The clinical implications of these cortical changes remain uncertain, but patients with less cognitive reserve may be more vulnerable to developing cortical abnormalities when exposed to medication or other disease-related biological factors.